Implementasi Kebijakan Program Makan Bergizi Gratis sebagai Pendorong dan Pembangunan Ekonomi Lokal - Raihan A. Hanasi; Izzatunnisa Akuba; Israh Miranti Wahab; Cipta Monoarfa; Muhajir Riza M. Ahmad; Alya Putri Pantoiyo (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study discusses the implementation of the Free Nutritious Meal Program (MBG) and its impact on local economic development. Using a literature review method, the research examines various sources discussing the effectiveness of the MBG program, operational challenges, and its contribution to the community. The study findings show that the success of MBG is influenced by several factors, including the stability of local food supplies, clarity of standard operating procedures (SOP), and the commitment of implementers at the school and regional government levels. This program has proven to stimulate the local economy by increasing the demand for local agricultural commodities, involving catering SMEs, and creating a multiplier effect that strengthens economic activities in the community. Additionally, MBG can increase the purchasing power of local communities and open up job opportunities in the food and distribution sectors. However, the implementation of MBG still faces challenges such as fragmented authority among institutions, limited infrastructure, and regional capacity variations. Overall, this program has dual potential as both a nutritional improvement effort and a local economic empowerment tool. To optimize MBG, strong coordination between central and local governments and implementers on the ground is essential. With adequate institutional readiness, MBG can become an effective instrument for regional development and local economic strengthening.